Graft-induced variations on morphological, biochemical and molecular parameters in apple (Malus x domestica Borkh.) (Indian Journal of Experimental Biology (IJEB), 2021)
Though grafting in plants is in practice since ages only limited information is available on the graft-inducedmorphological, biochemical and molecular variations. The mechanism(s) by which rootstocks influence scion vegetativegrowth and development, and vice versa, are not fully understood. Therefore, in the present investigation, we studied graft-induced variations in different apple stionic combinations using scion (Scarlet Gala and Red Fuji) and rootstocks (MM111,MM106, M7, M9 and M26). Under morphological variations, significant difference was found in all the parameters viz. leafarea, shoot length, internodal length and fruit characters except petiole length and fruit firmness. Likewise, significantdifference was also observed in the subjected stionic combinations based on total phenolic contents, total free amino acids andperoxidase enzyme activity. These results were further validated using DNA based molecular markers SSR. However, nopolymorphism was observed in both the stionic combinations at DNA level. These results imply that rootstocks may influencemorphological and biochemical parameter of the scion during graft-union but it does not influence genetic constitution of scionat DNA level. Further studies at RNA or protein level are required to unravel the reasons behind these variations.